The Association between Total Energy Expenditure and Cognitive Function in Convalescent Patients with Cerebrovascular Disease - Kojima, Maki; Nagano, Akinori (International Journal of Sport and Health Science, 2018)
[Objective] It has been reported that everyday physical activity, exercise, and physical fitness in older adults can affect their cognitive function. However, to our knowledge, no empirical evidence of this effect has yet been reported in convalescent patients with cognitive impairment resulting from cerebrovascular disease. Therefore, for such patients, it is important to investigate this issue to ensure optimal amelioration of their cognitive impairment during rehabilitation. The aim of this study was to estimate the amount of total energy expenditure during hospitalization, and to investigate the association between total energy expenditure and cognitive function in convalescent patients with cerebrovascular disease.[Methods] We recruited 24 patients (16 men and 8 women; average age 68.8±10.6 years) with cerebrovascular disorders. The total energy expenditure of each subject per day was estimated by the factorial method for five months. Cognitive function was assessed using items on the Functional Independence Measure (FIM).[Results] Both total energy expenditure and cognitive items on the FIM increased significantly (p<0.001) during the five-month period. A significant correlation was found between them (r=0.294, p=0.001), and the two showed a significant partial correlation (r=0.221, p=0.016) when weight was used as a control variable. There was also a significant partial correlation between the gain in total energy expenditure and the gain in the cognitive items on the FIM when the baseline score for cognitive function was used as a control variable (3 months: r=0.466, p=0.044; 5 months: r=0.485, p=0.035).[Discussion] We conclude that there is a relationship between total energy expenditure and cognitive function in convalescent patients with cerebrovascular disease.